Quality of Life Among Independent Elderly Residents in A Nursing Home in Banten Province, Indonesia - Yosi Marin Marpaung (GLOBAL HEALTH SCIENCE GROUP, 2024)
The elderly group, particularly those in nursing homes, is at a higher risk of experiencing a lower quality of life compared to elderly individuals who live at home or within the community. Therefore, monitoring the quality of life in nursing homes is essential to assess the wellbeing of the elderly and provide input for more targeted efforts to meet their needs. Objective: This study aims to provide information on the quality of life of the elderly, focusing specifically on the independent elderly group at nursing home X, located in Pamulang, Banten Province. Method: The study employed a quantitative approach with a cross-sectional design. A total of 45 out of 51 independent elderly individuals residing at nursing home X during the study period were involved. The WHOQoL-BREF instrument was used to measure the quality of life. Results: The findings revealed that the overall average quality of life score was categorized as good (60.2 ± 8.65). However, the average scores for each domain were as follows: physical domain 53.8 ± 10.6, psychological domain 59.2 ± 9.77, social relationship domain 61.7 ± 16.45, and environmental domain 66.1 ± 11.37. These scores indicate that the quality of life in the physical and psychological domain was predominantly unsatisfactory. Furthermore, the quality of life in the social domain also demands improvement. In addition, this study found a significant relationship between the quality of life and both the educational background (pvalue=0.009) and economic status (pvalue=0.025) of the elderly. Conclusions: Efforts to improve physical well-being require serious attention at nursing home X. Additionally, psychological, and social support initiatives are necessary. Further research exploring the challenges within each domain in greater depth and developing integrated interventions in collaboration with various stakeholders, including partners of the nursing home, is essential to enhance the well-being of the elderly.